2017
DOI: 10.3389/fpsyg.2017.00026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the SLC6A3-DAT1 Gene on Multifaceted Measures of Self-regulation in Preschool Children

Abstract: Development of self-regulation, the capacity to voluntarily modulate thoughts, emotions and actions is strongly related to the maturation of the dopamine-mediated executive attention network (EAN). The attention control processes associated with the EAN greatly overlap with efficiency of the executive functions and are correlated with measures of effortful control. Regulation of dopamine levels within the EAN, particularly in the basal ganglia is carried out by the action of dopamine transporters. In humans, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Future research is warranted to examine this possibility. This indirect pathway is also consistent with the view that genes involved in the dopamine system are related to self-regulation and emotional processes (Cómbita et al, 2017; Salgado-Pineda et al, 2005) and play an important role in maternal behavior (Bridgett et al, 2015; Numan, 2010). It appears that mothers with the DRD4 long allele have greater difficulty regulating their emotions, which undermines their ability to respond sensitively to their infants’ needs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Future research is warranted to examine this possibility. This indirect pathway is also consistent with the view that genes involved in the dopamine system are related to self-regulation and emotional processes (Cómbita et al, 2017; Salgado-Pineda et al, 2005) and play an important role in maternal behavior (Bridgett et al, 2015; Numan, 2010). It appears that mothers with the DRD4 long allele have greater difficulty regulating their emotions, which undermines their ability to respond sensitively to their infants’ needs.…”
Section: Discussionsupporting
confidence: 89%
“…Emotion regulation may also serve as a mediating pathway through which DRD4 affects maternal sensitivity. Prior research has demonstrated that dopamine and dopamine-related genes play important roles in self-regulation (Cómbita, Voelker, Abundis-Gutierrez, Pozuelos, & Rueda, 2017) and emotional processes (Salgado-Pineda, Delaveau, Blin, & Nieoullon, 2005). Numerous studies have examined the role of DRD4 in self-regulation, largely focusing on cognitive and attentional self-regulation in clinical samples of children with attention-deficit/hyperactivity disorder and yielding inconsistent findings regarding main effects of DRD4 on self-regulation (e.g., Johnson et al, 2008; Langley et al, 2004).…”
Section: Maternal Sensitivity and The Role Of Drd4mentioning
confidence: 99%
“…The gene encodes a dopamine transporter ( DAT ), which is a member of the sodium- and chloride-dependent neurotransmitter transporter family, and provides rapid clearance of dopamine [ 66 , 67 ], which mediates the reuptake of dopamine from the synaptic cleft [ 68 ]. Cómbita et al (2017) determined whether SLC6A3/DAT1 gene contributed to individual differences in children’s self-regulation skills [ 69 ]. They evaluated self-regulation skills and cognitive tasks such as conflict processing, inhibitory control, and intelligence assessments in 127 children at ages 4 and 6 in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis published in 2016 addressing studies performed in healthy subjects did not find any association between DAT VNTR and different cognitive functions, such as executive functions, inhibition, attention, and long-term declarative memory [ 92 ]. A study performed in children aged 3 to 5 years old addressing the presence of the 9-repeats and 10-repeats alleles revealed that the presence of the 10-repeat allele of the DAT gene is associated with diminished ability to voluntarily regulate reactivity in healthy children [ 93 ]. A recent study on both ADHD and healthy children reported an effect of the specific genotype in the performance of children on attentional switching when studying the whole research sample, in which children carrying the 9-repeat allele performed worse than those carrying the 10-reapet homozygous or the 10-repeat/11-repeat heterozygous allele [ 91 ]…”
Section: Genetic Factors Associated With Adhdmentioning
confidence: 99%